Sharia Financing And Community Economic Empowerment - Faturahman, Imam; Mandasari Hatta, Irma; Apriana, Agung (Lafadz Jaya Publisher, 2023)
This research aims to determine the role of Sharia financing and community economic empowerment. The research method used in this research is a qualitative method. The research results show that the Islamic perspective views sharia-based economic financing as a solution that can improve the economy of the people. In the Islamic view, sharia-based economic financing is a fairer and more sustainable way of developing the economy. In the sharia financing system, profits are not obtained from interest, but from a share of the business profits generated. Apart from that, sharia financing also applies the principle of sharing risks between capital owners and entrepreneurs. As an alternative financing, sharia banks can help improve the people's economy by providing financing in accordance with sharia principles. Apart from that, Islamic banks can also aid entrepreneurs to gain access to markets and better business opportunities. Sharia banks have a different economic mechanism from conventional banks, which are based on sharia principles and encourage the economic development of the people.